The relevance of economic complexity and economic globalization as determinants of energy demand for different stages of development - Doğan, Buhari; Ghosh, Sudeshna; Shahzadi, Irum [UNESP]; Balsalobre-Lorente, Daniel; Nguyen, Canh Phuc (Elsevier, 2022)
This study adds to the literature on energy studies on exploring for the first time to the best of our comprehension the importance of alternative measures of economic globalization indicators on energy-based demand in the context of economic complexity dynamics for 1971 to 2018 across a panel set of 63 countries classified as high-income (HIE), upper-middle-income (UME) and lower-middle-income countries (LME). Empirical results based on the panel ARDL model demonstrate i) the long-run relationships between economic complexity, economic globalization with energy demand; ii) economic complexity appears to increase energy-based demand in the short run, but it would reduce energy-based demand in the long run; iii) economic globalization is found to have decreasing effects in the short run and increasing effects in the longer run-on energy demand in LMEs and UMEs, while it has mixed effects in HIEs. The results suggest that policies supporting economic complexity would be a good strategy to aim at economic development while controlling for the increasing effects of globalization on energy demand to achieve long-term sustainable development.
Keywords: Country-classification; Economic complexity; Economic globalization; Energy; Panel ARDL method